An analytical method for construction of a fundamental portfolio - Kliber, Paweł; Rutkowska-Ziarko, Anna (Analityczna metoda wyznaczania portfela fundamentalnego, 2019)
The classical models used for the construction of an investment portfolio do not take into account the fundamental values of the companies in question. The model of a fundamental portfolio adds this dimension to the classical criteria of profitability and risk. It is assumed that an investor selects stocks according to their attractiveness measured by some fundamental values of companies. In the paper the authors propose an analytical solution of the optimization problem of constructing a fundamental portfolio and present empirical examples of the calculation of fundamental portfolios of stocks listed on the Warsaw Stock Exchange
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 25-36
Keywords: portfolio analysis; fundamental value; multicriterial choice; fundamental portfolio; analiza portfelowa; wartość fundamentalna; wybór wielokryterialny; portfel fundamentalny